2021
DOI: 10.3390/jcm10040636
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of Seasons with Inflammation, Red Meat, Fruit, and Vegetable Intakes, Cardio-Metabolic Health, and Smoking Status among Breast Cancer Survivors

Abstract: Seasons can affect human inflammatory status and the occurrence of diseases, and foods may also have differential impacts on inflammation across seasons; however, few studies have investigated whether there are independent and joint impacts of seasons and red meat, fruit and vegetable intakes on inflammation in breast cancer survivors. We conducted a cross-sectional study by leveraging a large cohort, the Women’s Healthy Eating and Living (WHEL) study. The WHEL study comprised primarily early stage breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Two relevant limitations are the non-randomized design and the 6-month delay in starting the control group (although the follow-up durations were equivalent). While our findings indicate a more favourable 1-year trajectory of hs-CRP in the intervention group, this result may have been influenced by seasonal changes [ 59 ], although seasonal effects on hs-CRP are uncertain [ 60 ]. While a significant hs-CRP decrease from baseline to 1 year was observed in the intervention group and no significant change was observed in the control group (even though baseline levels in the control group were higher), seasonal influences remain a potential confounder.…”
Section: Discussionmentioning
confidence: 99%
“…Two relevant limitations are the non-randomized design and the 6-month delay in starting the control group (although the follow-up durations were equivalent). While our findings indicate a more favourable 1-year trajectory of hs-CRP in the intervention group, this result may have been influenced by seasonal changes [ 59 ], although seasonal effects on hs-CRP are uncertain [ 60 ]. While a significant hs-CRP decrease from baseline to 1 year was observed in the intervention group and no significant change was observed in the control group (even though baseline levels in the control group were higher), seasonal influences remain a potential confounder.…”
Section: Discussionmentioning
confidence: 99%
“…To provide a further explanation for these findings, DII scores were adapted to explain the underlying strategies, since DII scores are based on dietary data sets collected from a dietary survey among the participants in that study, hence they could reflect the activation of oxidative stress and the inflammatory immune response related to specific food parameters (41) . The production of TNF-α, IFN-γ, IL-2 and IL-6 is mediated by proinflammatory diets high E-DII foods, corresponding with higher intake of refined grains, dairy products, red meats, soft drinks, sweets and desserts and lower consumption of whole grains, vegetables and fruits (42)(43)(44) . Nevertheless, the consumption of red meat across tertiles E-DII among cases in this study was parallel.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that high vegetable intake, particularly green leafy and cruciferous vegetables, correlated with lower levels of white blood cell counts [ 34 ]. The anti-inflammatory effect of vegetable assumption could be explained considering their content in polyphenol compounds with antioxidant effect, folate, and flavonoids [ 35 ], and through their restoration of water loss and electrolyte balance function [ 36 ]. Moreover, the high dietary fiber content supports gut health and the growth of microbial species which potentially modulate the production of pro-inflammatory chemokines and cytokines [ 37 ].…”
Section: Introductionmentioning
confidence: 99%